1994
DOI: 10.1002/j.1460-2075.1994.tb06787.x
|View full text |Cite|
|
Sign up to set email alerts
|

Ribozyme-mediated cleavage of the MDR-1 transcript restores chemosensitivity in previously resistant cancer cells.

Abstract: How cancer cells become resistant to chemotherapy is not completely understood, but it is believed that resistance is usually associated with overexpression of drug resistance genes. Drug resistance mediated by the MDR‐1 gene is the first well characterized form of drug resistance in human cancer. MDR‐1 encodes a phosphoglycoprotein, P‐GP, that serves as an energy‐dependent drug efflux pump, reducing intracellular drug accumulation and thereby cytotoxicity. We have used ribozymes to reverse the multiple drug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Therefore, it is reasonable to assume that at simi lar doses RZs will be more efficient in eliminating their target molecule than ODNs. This hypothesis has been experimen tally confirmed [9,10].…”
Section: Ribozymessupporting
confidence: 57%
“…Therefore, it is reasonable to assume that at simi lar doses RZs will be more efficient in eliminating their target molecule than ODNs. This hypothesis has been experimen tally confirmed [9,10].…”
Section: Ribozymessupporting
confidence: 57%
“…Previously, it has been reported that the retention of rhodamine 123 correlated well with the function of pgp-170 (Ludescher et al, 1992;Kiehntopf et al, 1994;Petriz and Garcia-Lopez, 1997;Salvioli et al, 1997). Therefore, retention of rhodamine 123 can be used as an indicator of pgp-170 function.…”
Section: Functional Assay Of Mdr1 Transportermentioning
confidence: 94%
“…rhodamine 123 in tumour cells with overexpressed pgp-170 was significantly reduced as compared to the MDR antagonist-treated tumour cells (Watt et al, 1990;Chaudhary and Roninson, 1991;Kiehntopf et al, 1994). The other Paclitaxel resistance type includes TRAG-1-5 (Paclitaxel resistance-associated gene 1-5) (Duan et al, 1997), p53 expression (Catherine et al, 1995) (Vikhanskaya et al, 1998), alteration of β-tubulin isoform (Dumontet et al, 1996), changes in the level of intracellular glutathione (Liebmann et al, 1993), or cell growth morphology (Frankel et al, 1997).…”
mentioning
confidence: 98%
“…For the exogenous application, ribozymes are delivered into cells by microinjection (10) or transfection (21). In the latter case, CaCl 2 or cationic liposomes have been mostly used as transfection reagents.…”
mentioning
confidence: 99%